TURNOVER INTENTION IN THE CEMENT INDUSTRY: A mediating model evaluation for future mitigation - Rini Adri Yanti; Harif Amali Rivai; Hendra Lukito (Journal Publicuho, 2023)
In the industrial sectors, retaining millennial employees by optimizing organizational support and suitability of workload is important to maintain the company's existence through human resources management, especially in the cement industry which requires employees with high-level integrity due to heavy work intensities. Therefore, this study was conducted to analyze and determine the effect of perceived organizational support and workload on turnover intention, by using the mediating contribution of job satisfaction to permanent millennial employees in one of the cement industries in Indonesia. Recorded, as many as 100 permanent millennial employees from various departments have participated. In terms of feedback data responses, were analyzed with the assistance of IBM SPSS software and Smart-PLS's latest version. Results found that fifth-relationships are in line with the research expectations while not to the other two. A quantitative approach with an explanatory design was used, in which the data were collected through online method distribution with the assistance of Google-form questionnaires. In the techniques of analysis, this study uses Smart-PLS software's latest version to assist the structural equation model (Average Variance Extracted > 0,5, Composite Reliability > 0,7, HTMT < 0,85, and R-square > 0,33), and second-order path-analysis (T > 1,96 & P ≤ 0,05) while IBM SPSS latest version used to descriptive analysis.